Urban–rural divergence of wintertime organic aerosol molecular fingerprints in PM2.5 revealed by FT–ICR MS - Shanshan Tang; Jintian Zhang; Yuansheng Wang; Jitao Lv; Lei Liu; Weijun Li; Yawei Wang (Atmospheric Environment, 2026)

A proton-relay strategy with K-modulated N/P proton pairs over Ru-based catalysts for efficient ammonia decomposition - Shuyu Chen; Rui Chen; Liang Wang; Haibo Tang; Rui Wang; Tian Tian; Yawei Zhou; Zihan Meng; Haolin Tang (Chemical Engineering Journal, 2026)

Efficient removal of N-nitrosodimethylamine and triclosan by nFe@Fe3O4 nanocomposites: Enhanced generation of active hydrogen atoms - Ying Han; Wanqing Zhao; Xiaoping Zheng; Chuwei Li; Lingyun Tang; Tengfei Zhang; Yawei Xie; Hongyuan Liu (Journal of Environmental Chemical Engineering, 2026)

Atmospheric reaction molecular network suggests transformation-driven chemodiversity of secondary organic aerosols - Feifei Li; Jitao Lv; Shanshan Tang; Qiurui Zhang; Yiru Qin; Qiying Nong; Xianwei Wang; Yongshun Huang; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2026)

Cover crops potentially enhance soil organic carbon sequestration to offset greenhouse gas emissions without yield penalty towards net-zero rice agriculture - Ruitao Lou; Yong Li; Zhenghan Li; Zhifeng Xu; Yu Tang; Xiangping Jin; Junzeng Xu; Yawei Li; Yong He; Qianjing Jiang (Agriculture, Ecosystems & Environment, 2026)

Machine learning reveals molecular substructure drivers of organic contaminant translocation in crops - Haodong Lang; Yang Cui; Wen Liu; Shanshan Tang; Wei Gao; Chengyu Zhai; Jing Lu; Yawei Wang (Science of The Total Environment, 2026)

An mRNA microsphere vaccine inhibiting overactivation of DNA sensing mechanisms - Fangke Zhang; Jiancheng Zheng; Fei Wang; Yaping Zhuang; Yunkai Tang; Juan Wang; Yawei Du; Wei-Li Zhao; Min Lu; Weiguo Hu; Wenguo Cui (Science Bulletin, 2026)

Corrigendum to “Genomic and functional characterization of the lect2 gene from Siniperca chuatsi” [Fish Shellfish Immunology 107 (2020) 146–155] - Yawei Shen; Ming Cao; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen; Yanhui Bi (Fish & Shellfish Immunology, 2026)

A general pyrolysis strategy to construct rare-earth oxide-stabilized high-density Ru single atom catalysts for efficient thermocatalytic CO2 methanation - Yunxiang Tang; Yanan Zhang; Aihuan Sun; Hao Wang; Yawei Miao; Zhengyi Yang; Yunqian Tang; Qun Li; Shujiao Wang; Lingheng Kong; Yinfeng Han (Chemical Engineering Journal, 2025)

Improved degradable, mechanical, and osteoimmunity-regulating performances of additively manufactured Zn-Mg alloy with heterogeneous microstructure for augmented bone regeneration - Zhengjun Lin; Luxin Liang; Yawei Li; Yanlin Wu; Jing Li; Bing Wang; Chao Chen; Tang Liu (Chemical Engineering Journal, 2025)

Self-assembling biocompatible core-shell nanocapsules with versatile surface functionalities for precise pesticide delivery - Chunlin Yang; Zaiyu Lu; Chunhui Zhou; Xiang Yao; Yawei Tang; Xiuxia Li; Junjun Wang; Lihong Zhang (Chemical Engineering Journal, 2025)

Polysaccharide-gated metal–organic framework nanoparticles for pH-triggered site-specific delivery and enhanced fungicide bioavailability - Chunlin Yang; Yawei Tang; Xiang Yao; Peijie Hu; Zaiyu Lu; Jinjing Xiao; Lihong Zhang; Haiqun Cao (Chemical Engineering Journal, 2025)

Synchronised removal of nitrogen and sulphate from rubber industrial wastewater by coupling of Sulfammox and sulphide-driven autotrophic denitrification in anaerobic membrane bioreactor - Ishanka Wimalaweera; Fumin Zuo; Qihe Tang; Qianwen Sui; Shameen Jinadasa; Sujithra Weragoda; Tharindu Ritigala; Rohan Weerasooriya; Yawei Wang; Hui Zhong; Madhubhashini Makehelwala; Yuansong Wei (Bioresource Technology, 2025)

Versatile plant genome engineering using anti-CRISPR-Cas12a systems - Yao He; Shishi Liu; Long Chen; Dongkai Pu; Zhaohui Zhong; Tang Xu; Qiurong Ren; Chuan Dong; Yawei Wang; Danning Wang; Xuelian Zheng; Fengbiao Guo; et al. (Science China Life Sciences, 2024)

Optimized multi-point hemispherical grid model with adaptive grid division based on the prior information of multipath error - Xuan Zou; Yawei Wang; Zhiwen Wu; Weiming Tang; Chen Zhou; Zhiyuan Li; Chenlong Deng; Yangyang Li; Yongfeng Zhang (Advances in Space Research, 2024)

High throughput identification of carbonyl compounds in natural organic matter by directional derivatization combined with ultra-high resolution mass spectrometry - Shiyang Yu; Shanshan Tang; Jitao Lv; Feifei Li; Zichun Huang; Lixia Zhao; Dong Cao; Yawei Wang (Water Research, 2024)

A real-time accuracy prediction model on time-relative positioning method considering the correlation of position increment errors - Xuan Zou; Zhiyuan Li; Weiming Tang; Yawei Wang; Yangyang Li; Siyu Zhang; Yongfeng Zhang (GPS Solutions, 2024)

The silent threat: Nanopolystyrene and chrysene pollutants disrupt the intestinal mucosal barrier, new insights from juvenile Siniperca chuatsi - Tiantian Chen; Rahma Sakina Said Aly; Yawei Shen; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen (Science of The Total Environment, 2024)

Facet-dependent transformation and toxicity of nanoscale zinc oxide in the synthetic saliva - Xiang Zhang; Yunpeng Huang; Jikun Wang; Jie Tang; Yang Mei; Nali Zhu; Zhigang Li; Lingxiangyu Li; Yawei Wang (Journal of Environmental Sciences, 2024)

Multipath error mitigation method considering NLOS signal for high-precision GNSS data processing - Xuan Zou; Ruinan Fu; Jian Tang; Yawei Wang; Xiaoyun Fan; Zhiyuan Li; Chenlong Deng; Yangyang Li; Weiming Tang (GPS Solutions, 2023)

Examining the impacts of implicit economic policy on urban environmental pollution: Unveiling pathways for sustainable recovery - Ya Yang; Mengru Zhou; Yawei Hou; Run Tang; Bo Liu; Yue Deng (Resources Policy, 2023)

Experimental and theoretical study on the suppression effect of water mist containing dimethyl methylphosphonate (DMMP) on hydrogen jet flame - Zhirong Wang; Hui Xu; Yawei Lu; Zhenhua Tang; Rujia Fan (Fuel, 2023)

Water splitting, pollutant degradation and environmental impact using low-index faceted metal-based nanocrystals. A review - Xiang Zhang; Jie Tang; Nali Zhu; Lingxiangyu Li; Yawei Wang (Environmental Chemistry Letters, 2022)

Identification of HvLRX, a new dehydration and light responsive gene in Tibetan hulless barley (Hordeum vulgare var. nudum) - Junjun Liang; Haili Zhang; Ling Yi; Yawei Tang; Hai Long; Maoqun Yu; Guangbing Deng (Genes & Genomics, 2021)

A comparative analysis of navigation signals in BDS-2 and BDS-3 using zero-baseline experiments - Chenlong Deng; Shufeng Qi; Yangyang Li; Yawei Wang; Xuan Zou; Weiming Tang; Chi Guo (GPS Solutions, 2021)

Visualization of GNSS multipath effects and its potential application in IGS data processing - Weiming Tang; Yawei Wang; Xuan Zou; Yangyang Li; Chenlong Deng; Jianhui Cui (Journal of Geodesy, 2021)

Identification and candidate gene mining of HvSS1, a novel qualitative locus on chromosome 6H, regulating the uppermost internode elongation in barley (Hordeum vulgare L.) - Xi Pu; Yanyan Tang; Meihao Zhang; Tao Li; Xvebing Qiu; Juanyu Zhang; Jinhui Wang; Lilan Li; Zhao Yang; Yan Su; Haili Zhang; Junjun Liang; et al. (Theoretical and Applied Genetics, 2021)

Promoter methylation and expression of the rassf4 gene in Nile tilapia ( Oreochromis niloticus ) - Yawei Shen; Huiyang Li; Min Zhou; Shoujie Tang; Yan Zhao; Jinliang Zhao; Xiaowu Chen (Journal of Fish Biology, 2021)
Oreochromis niloticus RAS‐association domain family 4 ( rassf4 ) was specifically expressed in the ovaries. Immunohistochemistry results showed that Rassf4 was located in follicular cells. The methylation percentages of the promoter region (−734/−1012) of rassf4 in the ovaries and testes were 13.28% and 92.85%, respectively. Deleting the fragment of −734 to −1012 sites significantly reduced the basal activity of the rassf4 promoter to 62.33%, which indicated that this region was important for the transcription of the rassf4 gene. This study lays the foundation for further research on the function of fish rassf4 .

Tocilizumab for treating COVID-19: a systemic review and meta-analysis of retrospective studies - Meng Zhao; Jieyu Lu; Yihu Tang; Yawei Dai; Jingxin Zhou; Yanhu Wu (European Journal of Clinical Pharmacology, 2021)

Design of gas drainage modes based on gas emission rate in a gob: a simulation study - Xiaowei Li; Chaojie Wang; Yujia Chen; Jun Tang; Yawei Li (Arabian Journal of Geosciences, 2018)

Instantaneous BDS + GPS undifferenced NRTK positioning with dynamic atmospheric constraints - Xuan Zou; Yawei Wang; Chenlong Deng; Weiming Tang; Zongnan Li; Jianhui Cui; Chen Wang; Chuang Shi (GPS Solutions, 2018)

Transcriptome profiles reveal cold acclimation and freezing tolerance of susceptible and tolerant hulless barley genotypes - Hongjun Yuan; Xingquan Zeng; Zhihao Ling; Zexiu Wei; Yulin Wang; Zhenhua Zhuang; Qijun Xu; Yawei Tang; Nyima Tashi (Acta Physiologiae Plantarum, 2017)

Erratum to: Transcriptomics analysis of hulless barley during grain development with a focus on starch biosynthesis - Yawei Tang; Xingquan Zeng; Yulin Wang; Lijun Bai; Qijun Xu; Zexiu Wei; Hongjun Yuan; Tashi Nyima (Functional & Integrative Genomics, 2017)

Transcriptomics analysis of hulless barley during grain development with a focus on starch biosynthesis - Yawei Tang; Xingquan Zeng; Yulin Wang; Lijun Bai; Qijun Xu; Zexiu Wei; Hongjun Yuan; Tashi Nyima (Functional & Integrative Genomics, 2017)

A Single Nucleotide Polymorphism of Nud Converts the Caryopsis Type of Barley (Hordeum Vulgare L.) - Shuiyang Yu; Hai Long; Guangbing Deng; Zhifen Pan; Junjun Liang; Xingquan Zeng; Yawei Tang; Nyima Tashi; Maoqun Yu (Plant Molecular Biology Reporter, 2016)

Dominantly Inherited Myotonia Congenita Resulting from a Mutation That Increases Open Probability of the Muscle Chloride Channel CLC-1 - David P. Richman; Yawei Yu; Ting-Ting Lee; Pang-Yen Tseng; Wei-Ping Yu; Ricardo A. Maselli; Chih-Yung Tang; Tsung-Yu Chen (NeuroMolecular Medicine, 2012)

A Novel Method for Automatic Identification of Motion Artifact Beats in ECG Recordings - Yuewen Tu; Xiuquan Fu; Dingli Li; Chao Huang; Yawei Tang; Shuming Ye; Hang Chen (Annals of Biomedical Engineering, 2012)

Family history of malignancies and risk of breast cancer: prospective data from the Shanghai women’s health study - Briseis A. Kilfoy; Yawei Zhang; Xiao-Ou Shu; Yu-Tang Gao; Bu-Tian Ji; Gong Yang; Hong Lan Li; Nathaniel Rothman; Wong-Ho Chow; Wei Zheng (Cancer Causes & Control, 2008)